Trends Shaping Tomorrow's World: Forces in the Natural and Institutional Environments. - Cetron, Marvin J.; Davies, Owen (Futurist)
For almost half a century, Forecasting International has been tracking the forces that shape the future. Some two decades ago, these observations were codified into a list of trends that forms the basis for so much of the organization's work. For each of its projects, the particular circumstances of an industry or organization are compared with these general trends and their interactions are projected. This often facilitates the formation of a remarkably detailed picture of what lies ahead. A period trend report covering trends in energy, the environment, technology, management and institutions, and terrorism is presented.